Correction: Porous monoliths synthesized via polymerization of styrene and divinyl benzene in nonaqueous deep-eutectic solvent-based HIPEs. Issue 42 (29th June 2018) - Pérez-García, M. G.; Carranza, A.; Puig, J. E.; Pojman, J. A.; del Monte, F.; Luna-Bárcenas, G.; Mota-Morales, J. D.
Abstract : Correction for 'Porous monoliths synthesized via polymerization of styrene and divinyl benzene in nonaqueous deep-eutectic solvent-based HIPEs' by M. G. Pérez-García et al., RSC Adv., 2015, 5, 23255–23260.